Applications of Inorganic Coagulant for Typical Organic Contaminants Removal from Water: A Review - Tang, X.M.; Zheng, H.L.; Liang, J.J.; Teng, H.K.; Zhai, J.; Sun, Y.J.; Xie, W.Y.; Zhang, Z.A.; Yang, Q.Q. (Asian Journal of Chemistry, 2015)
Organic pollution has become one of the most serious environmental issues and it possesses a potential threat to human health. The coagulation-flocculation as a water treatment technology has been used in the removal of contaminant from the water. In this review, it represents the concentration of typical organic contaminants in the water as well as their treatment by traditional and novel inorganic coagulants. The coagulation mechanism is also discussed.